No tricks, just treats - Tijan; Daniels, J; Hunting, Helena; Sivec, Tara (St. Martin's Paperbacks, 2019)
“FALLEN CREST NIGHTMARE” by TIJAN Sam, Mason, and the rest of their gang enter a fun Halloween-themed weekend with pumpkin carving, a girls<U+2019> night out, and a haunted house<U+2015>until things take a turn into something far more sinister than they could have expected<U+2026> “SO MUCH MORE” by J. DANIELS Four couples from Alabama reunite on Halloween for an evening of thrills and chills. Between haunted mazes, sexy stolen moments, and good old-fashioned trick-or-treating, this Halloween promises surprises, shocks, and maybe even love for all. “GETTING DOWN” by HELENA HUNTING Ruby Scott wants to have a party! With the help of her best friend Amalie<U+2015>and Amalie<U+2019>s fiancé<U+2019>s budget<U+2015>the two of them throw a Halloween-inspired fund-raiser. But no event goes off without a couple of hitches.<U+2026> “THE PUMPKIN WAS STUFFED” by TARA SIVEC The Holiday family is coming together for Halloween. As Sam and Noel prepare for their upcoming life with a new baby, their crazy family and friends pull out all the tricks and treats and jack-o<U+2019>-lanterns to make sure this ghostly holiday is one to remember<U+2026>or, will it turn out to be one they<U+2019>d rather forget?